Child language brokering as a family care practice: Reframing the ‘parentified child’ debate - Crafter, Sarah; Iqbal, Humera (Children & society, 2022)
This paper explores the perspectives of 29 child language brokers living in the UK who interpret for their family following migration. They were presented with vignette stories depicting a potentially conflictual situation between a language broker, a parent and an adult ‘other’ in a position of power or authority. Drawing on debates about language brokering as a family care practice, the ‘parentified child’ and discussions about non‐normative childhoods, the analysis highlights how the role played by the adult ‘other’, coupled with a sometimes‐hostile sociocultural context, can exaggerate tensions or facilitate interactions in the parent–child relationship. The young people's views and experiences illuminate how they navigate these complexities.